Adventure tourism landscape assessing participation satisfaction and potential in Kerala - Ranjith, P.R (Govt. College Kodanchery, University of Calicut, 2025)
The Study focuses on finding out the level of awareness of tourists on various Adventure Tourism options, to identify the participation and satisfaction of tourists in respect of Adventure tourism, to identify the barriers of Adventure Tourism in Kerala, to examine the potentials of Adventure tourism in respect of Adventure Tourism. Adventure tourism sector is considered as one of the fastest growing niche segments of Alternative Tourism. Adventure Tourism is defined as “Adventure tourism involves exploration or travel with perceived (and possibly actual) risk, and it potentially requires specialized skills and physical exertion.” Adventure Tourism considered as the Niche segment of Tourism. When compared to other niche forms of tourism Adventure tourism involves any two of following three components namely physical activity, natural environment and cultural immersion. On the basis of difficulty Adventure Tourism activities are classified in to two Such as Soft Adventure Tourism activities and Hard Adventure tourism activities. Soft Adventure Tourism activities are the activities which is relatively less risk involved and which doesn’t need any specialised skill to perform. Hard Adventure Tourism activities are the activities which involves high risk and which require specialised skills or need the guidance of skilled person to participate in such activities. Another important classification is on the basis of surface which is classified as Land Based Adventure Tourism activities, Water Based Adventure tourism activities and Aerial Based Adventure Tourism activities. The research methodology of the study based on ‘Research Onion’ by Saunders et al. (2007), It is a conceptual framework that describes various stages and layers involved in conducting research. By using research onion, the researcher is able to create a comprehensive and good research design for the study. The study used both Primary and secondary data, the primary data has been collected from both Adventure Tourists and the Adventure Tourism providers by using two different Interview schedules. The secondary data was collected from various published sources. The primary data collected from tourists to understand various the awareness, participation of tourists on various adventure tourism activities and measure the level of satisfaction of tourists on facilities offered by Adventure Tourism Providers (ATPs). The data collected from Adventure Tourism Providers (ATPs) to measure the difference in the Accessibility of Adventure Tourism Providers (ATPs). The Analysis of Data Depicts that most of the Land Based Activities shows high level of awareness, Water Based activities shows mixed level of awareness where some activities are more aware where other activities are not that much aware, Some Aerial based activities shows significant level of awareness on the other hand, some other Aerial activities show very low level of Awareness. In case of soft and hard adventuretourism activities the tourists are more aware about Soft Adventure tourism activities when compared to Hard adventure Tourism activities. Adventure Tourism activities like Trekking, scuba diving, Flat water kayaking, Floating Bridge and Zipline shown high level of participation, and the Satisfaction of Adventure tourists on various facilities offered at the centre is considerably high. Most demographic factors like age, gender, nationality, education, occupation, and travel duration do not affect the satisfaction on Adventure Tourism, whereas, the frequency of travel does make a difference that people travelled more shown different levels of satisfaction when compared to occasional tourists. The analysis also shows that there is a negative correlation between Awareness and satisfaction indicating that when there is higher level of awareness slightly reduces satisfaction. The study found that the accessibility of facilities such as Airport, Hospital, Bus Station and Fire Station is varied between districts. The Adventure tourism is facing numerous challenges like lack of awareness and promotion, Inadequate infrastructure, Regulatory and policy gaps, Environmental concerns etc. On the other hand, Kerala has immense potentials like Higher scope for water based and Mountain based Adventure tourism activities, the development of adventure circuits and hubs etc. and to become as a promising Adventure Tourism Destination in the region. The findings demand infrastructure development, operator training, eco-cultural integration, and introduce digital tools to enhance services with this collaborating efforts and policies Kerala can emerge as a leading adventure tourism destination by supporting long term social and economic growth. Keywords: Adventure Tourism, Soft Adventure Tourism, Hard Adventure Tourism, Adventure Tourism Providers (ATPs), Adventure Circuits, Adventure Hubs.
Keywords: Adventure Tourism; Soft Adventure Tourism; Hard Adventure Tourism; Adventure Tourism Providers (ATPs); Adventure Circuits; Adventure Hubs.